A Comparative Efficacy of Atezolizumab plus Bevacizumab Versus Sorafenib in Advanced Hepatocellular Carcinoma: A Review - Kristin Talia Marbun; Juandy Jo (Fakultas Kedokteran Universitas Pelita Harapan, 2022)
Hepatocellular carcinoma (HCC) ranks sixth as the most common cancer and fourth as the most common cause of cancer-related death globally. The standard treatment for advanced HCC is by prescribing sorafenib, a tyrosine kinase inhibitor. Despite its moderate efficacy and concerning side effects, there is no better alternative to sorafenib to treat HCC. However, a new combination of atezolizumab (an inhibitor of PD-L1) and bevacizumab (an inhibitor of vascular endothelial growth factor), has shown a potential to surpass the efficacy of sorafenib. This review was written to provide an insight into pharmacodynamics of sorafenib and atezolizumab plus bevacizumab, effectiveness of sorafenib and the one of atezolizumab plus bevacizumab, utilization of atezolizumab plus bevacizumab in the clinical practice, as well as to argue that this combination can replace sorafenib as the standard palliative treatment for HCC.